Correlation between vitamin D and lipid profile in patients with ischemic stroke - Giri, Richa; Rai, Rohit; Verma, Rajendra Kumar; Verma, Shivendra (International Journal of Research in Medical Sciences, 2017)
Background: This study aimed to investigate the relationship between serum vitamin D level and lipid profile in ischemic stroke patients. Methods: 217 patients with ischemic stroke were selected for analysis between ages 45 and 80 years admitted at our hospital from January 2014 to December 2015. Measurement of serum vitamin-D concentration was made by electrochemiluminescence immunoassay. Confounding variables like diabetes, hypertension, smoking, alcohol, tobacco, BMI, CRP, S. uric acid, duration of sunlight exposure, prior history of drug intake or fracture and S. calcium were considered. 200 age and sex matched controls were taken. The source of data was questionnaires and multiple linear regression analysis and correlation analysis were used. Results: A positive correlation was seen between vitamin D and serum cholesterol, VLDL, LDL, triglycerides, cholesterol/HDL ratio and LDL/HDL ratio but inverse correlation between vitamin D and HDL. Conclusions: In ischemic stroke patients increase in vitamin D is associated with increase in atherogenic lipids.